DEVELOPMENT OF ALKALINE DRINK WITH WATERMELON - Shyamalee, M.A.I. (My University, 2016)
Attached

Alkaline drink can be categorized under non alcoholic, non carbonated beverage having pH above 7.0. It is maintained in-between 7.5-9.5 pH range. It can be developed as a natural drink or as an artificial drink which having several health benefits. Watermelon is one of the fruit having extremely alkaline properties with compared to other fruits. The development of alkaline drink using watermelon is the main objective of the study. In this study matured watermelon fruit is selected and the fruit juice is extracted. According to the parameters of the juice collected sugar syrup is prepared to get the final brix value of the drink. After adding all the ingredients the final drink is pasteurized after bottling. The experiment work was carried out to evaluate the organoleptic and physical properties such as colour, odour, taste, saltiness, sweetness, acidity and overall acceptability. pH, brix value and microbiological conditions were determined throughout the shelf life. Significant differences in pH were recorded after one month from the date of manufacture but significant differences of the brix values and microbiological safety were not recorded. The lime flavoured sample (i.e. 7.8 pH, 11.0 brix value) was selected as most acceptable product by acquiring highest mean rank.